1998
DOI: 10.1159/000017331
|View full text |Cite
|
Sign up to set email alerts
|

Ketone Bodies and Brain Glutamate and GABA Metabolism

Abstract: The effects of ketone bodies on brain metabolism of glutamate and GABA were studied in three different systems: synaptosomes, cultured astrocytes and the whole animal. In synaptosomes the addition of either acetoacetate or 3-OH-butyrate was associated with diminished consumption of glutamate via transamination to aspartate and increased formation of labelled GABA from either L-[2H5-2,3,3,4,4]glutamine or L-[15N]glutamine. There was no effect of ketone bodies on synaptosomal GAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 38 publications
1
35
0
2
Order By: Relevance
“…However, the production of the ketone beta-hydroxybutyrate could also be from increased lipolysis. Ketone production has also been shown to positively influence the production of GABA (Daikhin and Yudkoff, 1998). We also found changes in concentrations of metabolites such as citrate, glycerol and glycerate and in medium-chain fatty acids, including myristate (C14:0), palmitate (C-16:0), stearate (C-18:0) oleate (C-18:1).…”
Section: Resultsmentioning
confidence: 56%
“…However, the production of the ketone beta-hydroxybutyrate could also be from increased lipolysis. Ketone production has also been shown to positively influence the production of GABA (Daikhin and Yudkoff, 1998). We also found changes in concentrations of metabolites such as citrate, glycerol and glycerate and in medium-chain fatty acids, including myristate (C14:0), palmitate (C-16:0), stearate (C-18:0) oleate (C-18:1).…”
Section: Resultsmentioning
confidence: 56%
“…This interaction between metabolism of glucose and that of amino acids suggested to us (23,31,75,(138)(139)(140)(141)(142)) that administration of a ketogenic diet might alter brain handling of neuroactive compounds such as glutamate and GABA. Our rationale was that a dietary regimen that sharply limits carbohydrate intake and obliges a shift in cerebral respiration to fuels other than glucose would have far-reaching implications for the handling of amino acids.…”
Section: Brain Metabolism Of Glucosementioning
confidence: 97%
“…In addition to these effects, a ketogenic diet alters brain energy metabolism (23,26,31,59,86,99,(138)(139)(140)(141)(142). Ketone bodies may be a more efficient fuel than glucose in terms of energy produced per mole of oxygen consumed (99).…”
Section: Introductionmentioning
confidence: 99%
“…In KD-fed mice, the glucose consumption may not change, but the glucose oxidative metabolism may be decreased and compensated with ketone body oxidation. On the other hand, recent studies have shown that ketone bodies increased y-aminobutyric acid (GABA) synthesis and decreased aspartate synthesis in purified synaptosomes, cultured astrocytes, and in the whole brain of rats (47). DeVivo et al (36) also reported a decrease in aspartate concentration in the brains of KD-fed rats.…”
Section: Influence Of the Kd On Associative Learningmentioning
confidence: 99%